2020
DOI: 10.3389/fncel.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Secreting L-Cells Coupled to Sensory Nerves Translate Microbial Signals to the Host Rat Nervous System

Abstract: An intact gut epithelium preserves the immunological exclusion of "non-self" entities in the external environment of the gut lumen. Nonetheless, information flows continuously across this interface, with the host immune, endocrine, and neural systems all involved in monitoring the luminal environment of the gut. Both pathogenic and commensal gastrointestinal (GI) bacteria can modulate centrally-regulated behaviors and brain neurochemistry and, although the vagus nerve has been implicated in the microbiota-gut-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Probable pathways by which these effects occur are the activation of vagal afferences by indole and on the other hand, accumulation of oxidized indole derivatives like oxindole and isatin in the brain. Indole has been shown to activate gut mucosal L-cells to secrete glucagon-like peptide-1 (GLP-1), which then stimulates vagal afferent fibres, therefore presenting an indirect impact of indole on the CNS [156]. Oxindole is known to inhibit motor activity [155], invoke hypotension, loss of righting reflex and a reversible comatose state, while isatin is proposed an anxiogenic role by inhibiting monoamine oxidase (MAO) B and by producing antagonistic effects on benzodiazepine receptors in rodents [70].…”
Section: Aams and Psychiatric Disordersmentioning
confidence: 99%
“…Probable pathways by which these effects occur are the activation of vagal afferences by indole and on the other hand, accumulation of oxidized indole derivatives like oxindole and isatin in the brain. Indole has been shown to activate gut mucosal L-cells to secrete glucagon-like peptide-1 (GLP-1), which then stimulates vagal afferent fibres, therefore presenting an indirect impact of indole on the CNS [156]. Oxindole is known to inhibit motor activity [155], invoke hypotension, loss of righting reflex and a reversible comatose state, while isatin is proposed an anxiogenic role by inhibiting monoamine oxidase (MAO) B and by producing antagonistic effects on benzodiazepine receptors in rodents [70].…”
Section: Aams and Psychiatric Disordersmentioning
confidence: 99%
“…A study combining biophysics, genetics, pharmacology, and cell co-culture methods in organoids showed that enterochromaffin cells can sense microbial metabolites in the intestinal lumen and regulate the release of 5-HT to directly communicate with neurons through synaptic interactions [7]. Microbial metabolites and other derivatives produced by food fermentation (e.g., SCFAs and bile acids) can impact intestinal peptide hormone secretion from EECs and through the microbial-gut-brain axis, affect the nervous system, and regulate the host metabolism [96,97,128,129]. There is also evidence that microbiota composition is closely associated with many psychiatric disorders such as anxiety and depression, autism spectrum and neurodegenerative diseases including Parkinson's disease and Alzheimer's disease, and with [130][131][132].…”
Section: The Gut-brain Axismentioning
confidence: 99%
“…As application of Ex‐4 in the presence of IL‐6 resulted in enhanced calcium responses in submucosal neurons, 9 Ussing chamber studies were used to investigate the effects of Ex‐4, either alone or with IL‐6 on short‐circuit current (I Sc ), a measure of net ion transport across the colonic epithelium. Separately, addition of IL‐6 7 (103.6 ± 39.2, n = 7) and Ex‐4 30 (65.04 ± 26.3, n = 7) to the basolateral reservoir resulted in secretory currents with amplitudes larger than saline controls (16.87 ± 12.7 µA/cm 2 , n = 7). The secretory currents evoked by Ex‐4 with IL‐6 (161 ± 108.5 µA/cm 2 , n = 7) were larger than currents evoked by Ex‐4 alone ( p = 0.0016, Figure 1A).…”
Section: Resultsmentioning
confidence: 98%
“…We have reproduced the positive effects of GLP‐1 on gut function in the Wistar‐Kyoto rat model of IBS 9 and used healthy Sprague‐Dawley rats colons to further explore the mechanisms of action underlying these beneficial effects. We found that exendin 4 (Ex‐4), a longer‐lasting GLP‐1 receptor agonist, 29 decreased the amplitude of circular smooth muscle contractions, increased the amplitude of colonic secretory currents, and decreased barrier permeability 30 …”
Section: Introductionmentioning
confidence: 99%